The application of a deep convolution neural network for the automated delineation of the target and organs at risk in High Dose Rate Cervical Brachytherapy - Duprez, Didier Raphael Roger (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.